Rational Expectations and Econometric Practice. - Lucas, Robert E. (University of Minnesota Press, 1977)
Assumptins about how people form expectations for the future shape the properties of any dynamic economic model. To make economic decisions in an uncertain environment people must forecast such variables as future rates of inflation, tax rates, government subsidy schemes and regulations. The doctrine of rational expectations uses standard economic methods to explain how those expectations are formed. This work collects the papers that have made significant contributions to formulating the idea of rational expectations. Most of the papers deal with the connections between observed economic beha.